Legal risks management in the economic sphere - S. V. Yevdokimenko (Law and Safety)
A significant number of regulatory acts that determine economic activity leads to an increase in the risk of losses in the economic sphere. Thus, some norms of the laws may worsen economic results due to inadequate or misleading interpretation of the conditions of the activity that violates the country’s economic safety and requires its protection.